2015
DOI: 10.1160/th14-11-0954
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of dabigatran therapy in daily-care patients with atrial fibrillation

Abstract: The effectiveness and safety of dabigatran for stroke prevention in atrial fibrillation (SPAF) demonstrated in RE-LY needs to be confirmed in daily care. To evaluate treatment persistence, effectiveness and safety of dabigatran therapy in SPAF patients in daily care, we used data from an ongoing, prospective, non-interventional registry of more than 2,500 patients on novel oral anticoagulants in daily care. Between October 1, 2011 and February 28, 2013, a total of 341 SPAF patients receiving dabigatran were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(24 citation statements)
references
References 24 publications
(27 reference statements)
2
20
1
1
Order By: Relevance
“…Data from the Dresden NOAC Registry suggest that rates of major bleeding may be lower with rivaroxaban, apixaban and dabigatran therapy compared with VKA therapy [13, 16, 18, 90]. Moreover, these data show that real-life rates of major bleeding with rivaroxaban were similar (Dresden NOAC Registry [16, 102]) or lower (XANTUS [26]) compared with findings from ROCKET AF [16, 102].…”
Section: Vitamin K Antagonists Vs Direct Oral Anticoagulants: Outcommentioning
confidence: 82%
See 1 more Smart Citation
“…Data from the Dresden NOAC Registry suggest that rates of major bleeding may be lower with rivaroxaban, apixaban and dabigatran therapy compared with VKA therapy [13, 16, 18, 90]. Moreover, these data show that real-life rates of major bleeding with rivaroxaban were similar (Dresden NOAC Registry [16, 102]) or lower (XANTUS [26]) compared with findings from ROCKET AF [16, 102].…”
Section: Vitamin K Antagonists Vs Direct Oral Anticoagulants: Outcommentioning
confidence: 82%
“…DOACs were at least as good as, if not superior to, warfarin in terms of efficacy for the prevention of stroke in patients with non-valvular AF and also offered a better safety profile (all four major trials consistently indicated reduced rates of intracranial and fatal or life-threatening bleeding compared with the respective warfarin arm) [32, 52, 58, 102, 109]. Real-world evidence of DOACs is accumulating, and available data support the findings of the phase III clinical studies (for example [13, 15, 16, 18, 26, 117, 121]). In general, current guidelines recommend DOACs in preference to VKAs [27, 114] or as an alternative to VKAs [74, 94] for prevention of stroke or systemic embolism in patients with non-valvular AF.…”
Section: Introductionmentioning
confidence: 99%
“…We also observed a rate of myocardial infarction of 0.5 per 100 patients-years and a rate of VTE of 2.8 per 100 patient-years. Firstly, it is interesting that a cohort reported by Beyer-Westendorf et al from a population of primary-care AF patients with similar baseline stroke risk factors and similar stroke rate had no VTE events at all [2]. Thus, the risk of VTE in AF patients, especially when medically ill or frail, should not be neglected.…”
Section: Discussionmentioning
confidence: 99%
“…Direct oral anticoagulants (DOACs), including the direct thrombin inhibitor dabigatran and the direct factor Xa inhibitors rivaroxaban, apixaban, and edoxaban, have shifted the paradigm of anticoagulation treatment from routine drug monitoring and dose adjustment to a one-size-fits-all strategy, and changed clinical practice of oral anticoagulation. Real-world data have confirmed the efficacy and safety of DOACs for stroke prevention [2, 3]. However, in a hospital-based patient population with AF, comorbid conditions, comedications and surgical interventions may complicate treatment with anticoagulant drugs, which has not been specifically addressed in previous real-world investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The paper by Coleman et al 3 is one of a deluge of papers on real world observational data on the comparative effectiveness of the various non-Vitamin K antagonist oral anticoagulants (NOACs) against warfarin [8][9][10][11] , or against each other [12][13][14] . Many cohorts have had substantially larger sample sizes and, importantly, the present analysis provides no data on dabigatran despite the extensive real world data published for this drug 15 .…”
Section: Editorialmentioning
confidence: 99%